Spontaneous currents in Josephson junctions between unconventional superconductors and d-wave qubits: Сверхпроводимость и мезоскопические структуры - Kolesnichenko, Yu.A.; Omelyanchouk, A.N.; Zagoskin, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The modern physics of superconductivity can be called the physics of unconventional superconductivity. The discovery of the d-wave symmetry of the order parameter in high-temperature superconductors and the triplet superconductivity in compound Sr2RuO4 has caused a huge stream of theoretical and experimental investigations of unconventional superconductors. In this review we discuss novel aspects of Josephson effect related to the symmetry of the order parameter. The most intriguing of them is spontaneous current generation in an unconventional weak link. The example of a Josephson junction as a grain boundary between two disorientated d-wave or f-wave superconductors, is considered in detail. Josephson current–phase relations and the phase dependences of the spontaneous current, that flows along the interface are analyzed. The spontaneous current and spontaneous phase difference are manifestations of the time-reversal symmetry (Ƭ ) breaking states in the system. We analyzed the region of appearance of Ƭ -breaking states as function of temperature and mismatch angle. A review of the basics of superconducting qubits with emphasis on specific properties of d-wave qubits is given. Recent results in the problem of decoherence in d-wave qubits, which is the major concern for any qubit realization, are presented.